Effects of Covid-19 Vaccines on Mental Health of an Individual A Cross-Sectional Clinical Study - Mohsina Rabia Maruf, Aqsa Mumtaz, Javeria Khan, Uzma Hameed, Anil Kumar Wadhwani, Usman Naeem, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The mains and objectives of the study was to evaluate the impact of Covid’19 vaccination on mental health status. Practical Implications: The results of this cross-sectional clinical study have practical implications for the wider community. Encouraging Covid-19 vaccination can have a positive impact on both physical and mental health, and promoting vaccine uptake may lead to improved mental health outcomes for individuals. Such benefits can reduce the overall burden of mental health issues during the pandemic, which is beneficial to the community. Thus, public health campaigns should focus on the potential positive effects of Covid-19 vaccines on mental health to improve community well-being and promote vaccine acceptance.